Multicultural coexistence as a site of otherness and becoming self: A narrative of a multilingual - Kim, Sumi; Brutt‐Griffler, Janina (International journal of applied linguistics, 2023)
Identity is a subject of intense scrutiny in the field of Applied Linguistics. Of particular concern are issues of intersectionality of language and culture in the lives of minority groups. Yet, the empirical evidence in support of language and cultural identity (re)construction of ethnic minorities in Japan is far from conclusive. Drawing on a narrative inquiry approach, the present study seeks to shed light on multilingual identity construction and negotiation in different language contexts, as experienced by Riko, a third‐generation Japanese woman of Korean descent. Our analysis shows that Riko's multilingual identity is undermined in Japan and Korea where monoglossic ideologies are still prevalent. The sociohistorical and sociopolitical context of Japan and Korea does not allow her to have any middle ground, exacerbating the potential for multilingual identity conflicts. In contrast, Riko's US study abroad experience aids her in cultivating a critical and deeper understanding of being a multilingual citizen. Findings further highlight the role of English which enables her to transcend the challenges posed by her ethnicity. In light of our findings, we draw implications for the significance of developing greater global and cultural awareness in language education and academic programs. 초록 정체성은 응용언어학 분야에서 오랜 시간 동안 다양한 방법으로 연구되고 있는 주요 주제이다. 그중에서도 소수 민족의 삶에서 언어와 문화 간의 상호교차성은 중요 관심사로서 자리 잡고 있다. 그런데도, 여전히 일본에 거주하는 소수 민족의 언어와 문화 정체성 (재)형성에 관한 연구는 충분한 실증적 증거를 제시하지 못하고 있다. 본 연구는 내러티브 탐구 방법 을 통하여 재일 한국인 3세 리코의 다중언어 정체성 형성과 교섭을 다양한 언어 사용 맥락에서 살펴보았다. 연구 결과, 리코의 다중언어 정체성은 한국이나 일본과 같은 단일민족국가에 팽배해 있는 언어 패권에 의해 갈등이 일어나는 것으로 나타났다. 특히, 한일 관계 기저에 깔린 사회 역사적, 사회 정치적인 배경은 리코의 다중언어 정체성 형성 및 변화 과정에서 갈등을 악화시켰다. 이와는 반대로, 리코는 미국에서의 학습 경험을 통해 더욱더 비판적이고 깊이 있게 다중언어 정체성을 형성하고 교섭할 수 있었음을 보여 주었다. 또한, 이 과정에서 영어는 리코의 민족성에서 비롯된 문제점에서 벗어나는 데 중요한 역할을 하는 것으로 나타났다. 이러한 연구 결과를 토대로, 본 연구는 다문화 인식 및 역량 강화의 중요성을 제언함과 동시에 그에 상응하는 언어 교육과 프로그램 개발의 필요성을 논의한다. 키워드 정체성; 언어 교육; 다중언어주의; 내러티브 탐구; 자이니치 코리안